A study of menstrual health perceptions, practices and prevalence of premenstrual symptoms in school-going adolescent girls in Chandigarh - Vinod, Anuna; Thakur, J. S.; Rajagopal, Vineeth; Thankaraj Vijayammal, Nisanth; Thasneem, Bushra; Prashanth, Karthika (International Journal Of Community Medicine And Public Health, 2025)
Background: Menstruation is a universal physiological process, yet it remains shrouded in cultural taboos and misinformation, particularly in low- and middle-income countries like India. These barriers contribute to poor menstrual health awareness and suboptimal hygiene practices, impacting adolescent girls’ physical and psychosocial well-being. This study aimed to assess menstrual health perceptions, practices, and the prevalence of premenstrual symptoms (PMS) among adolescent girls in government schools of urban Chandigarh. Methods: A descriptive cross-sectional study was conducted among 100 adolescent girls (aged 15-18 years) attending two purposively selected government schools in urban sectors of Chandigarh. Data were collected using a structured questionnaire and analyzed using descriptive statistics and chi-square/Fisher’s exact test to explore associations. Results: The mean age of participants was 15.4 years. Premenarche awareness was reported by 63%, with mothers and sisters as the primary information sources (64%). Only 19% had good perception scores, and 34% reported good menstrual hygiene practices. While 94% used sanitary pads and 63% changed pads at school, 66% reported food restrictions and hesitance to discuss menstruation with male family members. PMS were common: 67% reported headaches, 62% breast pain, and 59% experienced anxiety or tension. Poor maternal education was significantly associated with poor perception among daughters (p=0.040). Conclusions: Despite good access to sanitary products and school-based hygiene facilities, substantial gaps persist in menstrual perception and practices. Cultural stigma, dietary restrictions, and limited awareness of PMS are prevalent. Targeted health education and supportive school environments are vital to improving menstrual health outcomes among adolescents.